Biological Functions and Therapeutic Potential of Autophagy in Spinal Cord Injury - Liao, Hai-Yang; Wang, Zhi-Qiang; Ran, Rui; Zhou, Kai-Sheng; Ma, Chun-Wei; Zhang, Hai-Hong (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an evolutionarily conserved lysosomal degradation pathway that maintains metabolism and homeostasis by eliminating protein aggregates and damaged organelles. Many studies have reported that autophagy plays an important role in spinal cord injury (SCI). However, the spatiotemporal patterns of autophagy activation after traumatic SCI are contradictory. Most studies show that the activation of autophagy and inhibition of apoptosis have neuroprotective effects on traumatic SCI. However, reports demonstrate that autophagy is strongly associated with distal neuronal death and the impaired functional recovery following traumatic SCI. This article introduces SCI pathophysiology, the physiology and mechanism of autophagy, and our current review on its role in traumatic SCI. We also discuss the interaction between autophagy and apoptosis and the therapeutic effect of activating or inhibiting autophagy in promoting functional recovery. Thus, we aim to provide a theoretical basis for the biological therapy of SCI.